2018
DOI: 10.1089/neu.2018.5663
|View full text |Cite
|
Sign up to set email alerts
|

A Mild Traumatic Brain Injury in Mice Produces Lasting Deficits in Brain Metabolism

Abstract: Metabolic uncoupling has been well-characterized during the first minutes-to-days after a traumatic brain injury (TBI), yet mitochondrial bioenergetics during the weeks-to-months after a brain injury is poorly defined, particularly after a mild TBI. We hypothesized that a closed head injury (CHI) would be associated with deficits in mitochondrial bioenergetics at one month after the injury. A significant decrease in state-III (adenosine triphosphate production) and state-V (complex-I) driven mitochondrial resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 57 publications
1
38
1
Order By: Relevance
“…It is a general finding that mitochondrial dysfunction, inadequate supplies of ATP, and oxidative stress are contributory factors in almost all forms of brain disease [60]. This has been reported for neurological conditions such as major depressive disorder [61], traumatic brain injury [62], Parkinson's disease [63], and for AD [64].…”
Section: Metabolismmentioning
confidence: 93%
“…It is a general finding that mitochondrial dysfunction, inadequate supplies of ATP, and oxidative stress are contributory factors in almost all forms of brain disease [60]. This has been reported for neurological conditions such as major depressive disorder [61], traumatic brain injury [62], Parkinson's disease [63], and for AD [64].…”
Section: Metabolismmentioning
confidence: 93%
“…In this experiment, we evaluated whether our 7-trial protocol was able to detect memory deficits in a mTBI model. In the past, it has been shown that the same animal model of CHI was memory impaired in a 6-arm RAWM when a 15-trial protocol and 2-day test [27, 36] and a 15-trial protocol and 4-day test [30] protocol were used. To compare differences between SHAM and CHI mice, we used the median of errors made during the 4-day test (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A major finding of our study was that the reduction of number of trials significantly separates the acquisition curves of CHI and SHAM mice and the sex had no effect on results. Previously, we demonstrated that CHI mice had memory impairment in a 6-arm RAWM at 2 week post-CHI in a 4-day protocol and 15-trial per day [30] or in 2-day protocol and 15-trial per day [27, 36]. However, due to the knowledge that training schedule and spacing of training sessions can impact learning ability [1013, 24, 25], we sought to determine if reduction of training increased the learning separation between mice affected by mTBI and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we report the results of the second statistical model without sex of the mice included in the model. We have shown that the sex of the mice affects response to the CHI for some variables [30]; thus, the data for the CHI experiments were disaggregated by sex.…”
Section: Plos Onementioning
confidence: 99%